The role of strategic flexibility in improving the efficiency of bank employees: Applied research (Journal of Accounting and Financial Studies ( JAFS ), 2025)
This research aims to study the relationship and impact between the independent variable strategic flexibility and the dependent variable employee efficiency, as the research problem was defined by the main question (Does strategic flexibility play a role in improving employee efficiency in banks?), as the research was applied in each of the banks (Ashur International, Middle East Iraqi Investment, Al-Mansour Investment), as it relied on the financial data and reports of these banks for the years (2019-2023) in analyzing and interpreting the data.The results showed that strategic flexibility is a key factor in improving employee efficiency in banks, as it contributes to enhancing productivity, stimulating innovation, and reducing operational errors, which leads to achieving a sustainable competitive advantage for banks in a dynamic and changing banking environment, in addition to the fact that continuous training programs help employees acquire new skills and improve their performance, which enhances their ability to interact with banking market variables.